Boosting Student Work Readiness: A Meta-Analysis of Soft Skills and Teaching Factory - Dede Syukrillah Rifai; Widodo Widodo; Hasbullah Hasbullah (Jurnal Pemberdayaan Masyarakat, 2025)
This study aims to systematically synthesize and evaluate empirical evidence concerning how soft skills and teaching factory (TEFA) programs jointly influence students’ work readiness across diverse educational settings. Employing a comprehensive meta-analysis design, this research integrates quantitative results from prior empirical studies to produce a more robust and generalizable estimation of the combined effect. The data used in this study were derived from 31 independent studies published between 2020 and 2025. The dataset consists of 23 studies focusing on soft skills and 8 studies on teaching factory programs. All data were analyzed using JASP version 0.19.3, employing both classic meta-analysis and random-effects models to account for heterogeneity across samples. The findings reveal a significant positive correlation between soft skills (r = 0.519) and teaching factory (r = 0.693) with work readiness (p 0.01). The results confirm that both factors strongly enhance employability and readiness to work in industrial contexts. Statistical confidence intervals and forest plots generated in JASP strengthen the empirical robustness of these conclusions. This meta-analysis makes a novel contribution by being the first to quantitatively evaluate the combined impact of soft skills and teaching factory programs on graduates’ employability in Indonesia. The evidence highlights the strategic importance of embedding these two elements into vocational and higher education curricula to strengthen graduates’ employability profiles and ensure their alignment with industry expectations.